Effects of a newly developed palm-based processing aid and curing systems on the physical properties of nitrile rubber composites - Hani Mohd Hanif; Yong, Kok Chong; Lee, Siang Yin (Penerbit Universiti Kebangsaan Malaysia, 2020)
Researches on developing renewable and eco-friendly processing aid are still on-going in the effort of replacing conventional petroleum-based processing aid. In this study, the effects of a palm-based processing aid (Bio) and curing systems on the physical properties of nitrile rubber (NBR) composites were evaluated. Curing systems studied were conventional (CV), semi-efficient (SEV) and efficient (EV) curing systems. It was found that regardless of the curing systems, the addition of Bio reduced the delta torque, cure rate index, glass transition temperature and loss tangent of the NBR composites. Reduction of delta torque by Bio resulted in lower tensile modulus (M100) and higher elongation at break (EB) of composites. Hardness, swelling index and compression set were also higher with the incorporation of Bio. The effects of curing system were also prominent in which using CV cure system leads to higher M100 and hardness and lower EB and compression sets. Excellent aging properties are crucial as it predicts the properties of the composite during service. After accelerated aging, results revealed that the effects of curing systems were significant on the retention of M100 and compression set of NBR composites where the SEV cured composites showed the highest retention of M100 and the lower compression set values. NBR composite with Bio, using a semi-efficient curing system was found to have the best aging properties compared to other composites.